If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(1)+y=-4
We simplify the equation to the form, which is simple to understand
2(1)+y=-4
Reorder the terms in parentheses
+(+2)+y=-4
Remove unnecessary parentheses
+2+y=-4
We move all terms containing y to the left and all other terms to the right.
+1y=-4-2
We simplify left and right side of the equation.
+1y=-6
We divide both sides of the equation by 1 to get y.
y=-6
| -(3a+6b)-(a-11b)= | | 5+2x-3x^2=0 | | x^2-13x-21=-7x-5 | | 10*5+66-56-12-510=x | | 148-5x=31x+20 | | 5a+6=4 | | 5x^2+10x-25= | | 37x(3*1.5)=4150 | | 4-5x=1.5 | | 3xy=4x-1 | | 12y+x=180 | | 2(2x-4)=12x | | 8-2x=x-2 | | x^2-14x+25=-3x-3 | | 0.4x+0.2=1 | | r-6=13 | | 15x-5=12x-8 | | -4y-4=-3y-8 | | 3=x^2-8x+15 | | x^3=3.9e-11 | | b-10=-16 | | 162-2x=43x+22 | | 9-p^2+8p-16=0 | | -38-4x=-6(1+6x) | | 9=3x+11 | | -5x+6=2x-8(4x-7) | | 5c^2+45c=0 | | 6+7w=10 | | 5c^2+45=0 | | 8w-5=0 | | 4w+7=100 | | 4xy=9 |